A (t, n) threshold quantum visual secret sharing. (20th June 2020) - Liu, Wenjie; Xu, Yinsong; Chen, Junxiu; Yang, Ching-Nung
Secure data sharing is a deserving topic in wireless sensor networks. In order to deliver the information securely, we propose a (t, n) threshold quantum visual secret sharing (QVSS) scheme based on Naor et al.'s visual secret sharing (VSS) scheme, which consists of two phases: sharing process and recovering process. In the firs process, the colour information of each pixel from the original secret image is encoded into an n × m-qubit superposition state, and then these qubits are distributed as shares to all participants, respectively. During the recovering process, at least t participants cooperate to collect these shares of each pixel together, then perform the corresponding measurements and recovering algorithm to recover the whole secret image. The proposed scheme has the advantage of single-pixel parallel processing that is not available in the existing analogous quantum schemes. In addition, the performance evaluation of the scheme is discussed theoretically, and its experiment implementation with IBM Q is conducted to demonstrate the practical feasibility.